Strategi Pengelolaan Media Sosial Spbu Pertamina Melalui Perencanaan Konten Editorial: Studi Pada Visi Agia Global - Bahar, Sylvania Lucky; Hidayat, Aceng (JURNAL MANAJEMEN PENDIDIKAN, 2026)
SOCIAL MEDIA MANAGEMENT STRATEGY OF PERTAMINA FUEL STATIONS THROUGH EDITORIAL CONTENT PLANNING: A STUDY AT VISI AGIA GLOBAL The development of social media has encouraged public service organizations to manage digital communication in a more structured and strategic manner, including Pertamina fuel stations as providers of public energy services. This study aims to analyze editorial content planning in the management of the @spbupertamina social media account by examining message design and audience interaction management. This research adopts a qualitative descriptive approach conducted through an internship program at PT Visi Agia Global, the agency involved in managing Pertamina fuel station social media. Data were collected through observation, interviews, and documentation, and analyzed using McGuire’s Message Processing Model as the primary theoretical framework and the Circular Model of SOME as a supporting operational framework. The findings indicate that editorial content planning is carried out systematically through the preparation of editorial calendars, theme determination, content format selection, publication scheduling, and content evaluation, which are designed to support the stages of audience message processing. In addition, audience interaction management is implemented in a structured and continuous manner through the cycle of share, optimize, manage, and engage. This study concludes that the integration of cognitively oriented message planning and cyclical social media management contributes to the effectiveness of Pertamina fuel stations’ digital communication as a public energy service.